Description of the universal model of design system - Sinenko, Sergey; Fakhratov, Mukhammet; Akbari, Mohammad Sharif (E3S web of conferences, 2019)
The article proposes one way to describe the design model. Definitions of the basic concepts of design are given. The design process is considered as a certain representation of the project for the construction of an object in all conditions. Design routes, design operations algorithms, including tools for evaluating user indicators, methods for determining design resources, describe it. The description forms are well known to everyone: maps, circuits, matrix, linear and network models, etc. A model of a design system is considered. The mathematical description of design procedures allows for a deeper analysis and generalization of design analysis data. In a production design system, which is a particular type of more general organizational system, each element has a specific production role associated with a particular person’s position in the production team. Thus, the elemental base of the design system is formed by subsystems, their elements, designers, and each designer carry out the conversion of resources. The model is illustrated by an example.The concepts introduced in the article and the proposed model make it possible to define organizational management as a process of redistributing the organizational system modules over technological and information modules.